Perceived quality of life using IMPACT-III in a sample of Colombian children with IBD in remission: a cross-sectional study - Parra-Izquierdo, Viviana (2025)
Introduction: No data on quality of life (QoL) in paediatric IBD in Colombia. The aim of this study was to determine QoL using the IMPACT-III questionnaire in a sample of patients from different centres. Materials and methods: Cross-sectional study of paediatric IBD patients followed in 3 centres in different cities, between June and November 2022. Eligible subjects were identified, information was collected on different dates, and the IMPACT-III questionnaire (score ranges from 35 to 175, with higher scores indicating better QoL) was administered once. Results: 33 patients were included. 23/33 (69.7%) female, mean age 14.9 (range 6-17.9) years. 94% with inactive or mild disease. 20 patients with ulcerative colitis (UC), 13 with Crohn's disease (CD). The median score in UC was 147 (122-152), while in CD it was 126 (105-135). Systemic symptoms and emotional functioning were most affected, with median scores of 13 (12-14) and 27 (20-31) in UC and 11 (9-11) and 23 (20-26) in CD. No statistically significant differences were observed. Conclusions: The quality of life of children with IBD is challenging due to several factors. More support and education is needed for these patients.